An atypical nonsebaceous lymphadenoma with diffuse lymphoepithelial differentiation - Min-Kyung Yeo; Da Mi Kim; Jin Man Kim (Wolters Kluwer Medknow Publications, 2016)
Nonsebaceous lymphadenoma is an uncommon salivary gland tumor. It consists of lymphoid and epithelial components that lack sebaceous differentiation. Herein, we present a 44-year-old woman with left a submandibular gland tumor. The tumor is well-circumscribed and solid without ductal or cystic formation. The epithelial cells intermingle with lymphoplasma cells. The epithelial cells show moderate cytologic atypia and a few mitoses with no viral infection. Histologically, the tumor had features of nonsebaceous lymphadenoma with unusual findings of nuclear atypia and marked lymphoepithelial differentiation. Atypical nonsebaceous lymphadenoma with diffuse lymphoepithelial differentiation is rare and important to recognize to avoid misdiagnosis.